Solid state synthesis of nanoporous insulating refractory oxides for microelectronic applications - Wu, Xiaoying. (2009)
SrY4(SiO4)3O single crystals with the oxyapatite structure were grown by the solgel method. This method is straightforward, inexpensive, versatile and it produces pure powders with controlled sized and morphology. The dependence of the nature of the phases was studied by varying several parameters such as the volumetric ratio of the acetic acid catalyst to TEOS and the calcination temperature. These two parameters affect the crystal structures and the purity of the oxides obtained after heat treatment in air.